Epidemiologic and clinical characteristics of severe burn patients: results of a retrospective multicenter study in China, 2011–2015. Issue 1 (23rd May 2018) - Tian, Hao; Wang, Liangxi; Xie, Weiguo; Shen, Chuanan; Guo, Guanghua; Liu, Jiaqi; Han, Chunmao; Ren, Licheng; Liang, Yi; Tang, Yong; Wang, Yuan; Yin, Meifang; et al.
Abstract: Background: Severe burns injury is a serious pathology, leading to teratogenicity and significant mortality, and it also has a long-term social impact. The aim of this article is to describe the hospitalized population with severe burns injuries in eight burn centers in China between 2011 and 2015 and to suggest future preventive strategies. Methods: This 5-year retrospective review included all patients with severe burns in a database at eight institutions. The data collected included gender, age, month distribution, etiology, location, presence of inhalation injury, total burn surface area, depth of the burn, the length of hospitalization, and mortality. SPSS 19.0 software was used to analyze the data. Results: A total of 1126 patients were included: 803 (71.3%) male patients and 323 (28.7%) female patients. Scalds were the most common cause of burns (476, 42.27%), followed by fire (457, 40.59%). The extremities were the most frequently affected areas, followed by the trunk. The median length of hospitalization was 30 (15, 52) days. The overall mortality rate was 14.21%. Conclusions: Although medical centers have devoted intensive resources to improving the survival rates of burn patients, expenditures for prevention and education programs are minimal. Our findings suggest that more attention should be paid to the importance of prevention and the reduction of injury severity. This study may contribute to the establishment of a nationwide burn database and the elaboration of strategies to prevent severe burns injury.